Pengembangan Materi Ajar Teks Fabel Melalui Media Lift The Flap Book Pada Siswa Kelas VII SMP Negeri 4 Medan - Sakila Lubis; Fitriani Lubis; Frinawaty Lestarina Barus (CV Edujavare Publishing, 2025)
This study aims to develop fable text-based teaching materials using the Lift the Flap Book media for seventh-grade students at SMP Negeri 4 Medan to increase their interest and understanding of fable texts. The background of this research is based on low reading interest and the limitations of conventional teaching methods that are unable to attract students' attention. The research was conducted using the Research and Development (R&D) method, adapting the Borg & Gall model, which includes problem identification, data collection, product design, validation, and design revision. The learning media was developed in the form of a digital leaflet using the Canva application, equipped with illustrations, animations, and interactive elements to enhance the learning experience. Validation results from material experts, media experts, and subject teachers indicate that this media is suitable for use in fable text learning. By using the Lift the Flap Book, students become more active, enthusiastic, and are helped to understand the structure and content of fable texts in depth. This research demonstrates that the development of visual and interactive learning media can be an effective solution to address the challenges of learning Indonesian in the digital era.